Agricultural Social Services and Land Transfer: A Multidimensional Analysis of Impacts on Land Allocation - Xi Yu; Walliams Ali; Dongmei Li (Land)
Land transfer is a crucial measure for optimizing cropland allocation and improving production efficiency, especially in resource-scarce countries. Drawing on a sample of 858 farmers from Sichuan Province, China, this study examines whether agricultural social services (ASSs) drive land transfer. Unlike previous research that focused on a single dimension, such as participation or scale, this paper examines land transfer behavior from three dimensions: participation, scale, and future transfer willingness. Using an endogenous switching regression model and a probit model, we analyze unique cross-sectional farm-level data collected from rural China. The results indicate that ASSs have a positive and significant impact on land transfer behavior: (1) ASS adoption increases the land transfer participation rate by 13.7%. (2) The transfer area increases by 74.34% due to ASSs. (3) The likelihood of future transfer increases by 4.2% with ASS adoption. These findings suggest that fostering a supportive environment for agricultural social services can enhance the land transfer market and contribute to sustainable modernization of the agricultural sector.